2018
DOI: 10.1002/ehf2.12251
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility of sacubitril–valsartan in a real‐world heart failure population: a community‐based single‐centre study

Abstract: AimsThis study aims to investigate the eligibility of the Prospective Comparison of Angiotensin Receptor–Neprilysin Inhibitor (ARNI) with ACE inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM‐HF) study to a real‐world heart failure population.Methods and resultsMedical records of all heart failure patients living within the catchment area of Umeå University Hospital were reviewed. This district consists of around 150 000 people. Out of 2029 patients with a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 29 publications
(53 reference statements)
2
46
1
1
Order By: Relevance
“…Just as in the PARADIGM‐HF trial, the proportion of women in our cohort was low. This might be due to several reasons, for instance initiation of sacubitril/valsartan requires a reduced LVEF and toleration of a substantial dose of ACE‐I or ARB, which might be more likely to occur in men . Additionally, it is well known that women tend to exhibit a more pronounced reverse remodeling response following initiation of heart failure therapies including pharmacotherapy or CRT …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as in the PARADIGM‐HF trial, the proportion of women in our cohort was low. This might be due to several reasons, for instance initiation of sacubitril/valsartan requires a reduced LVEF and toleration of a substantial dose of ACE‐I or ARB, which might be more likely to occur in men . Additionally, it is well known that women tend to exhibit a more pronounced reverse remodeling response following initiation of heart failure therapies including pharmacotherapy or CRT …”
Section: Discussionmentioning
confidence: 99%
“…This might be due to several reasons, for instance initiation of sacubitril/valsartan requires a reduced LVEF and toleration of a substantial dose of ACE-I or ARB, which might be more likely to occur in men. 25 Additionally, it is well known that women tend to exhibit a more pronounced reverse remodeling response following initiation of heart failure therapies including pharmacotherapy or CRT. 18 Although cardiologists should be convinced about the compelling benefit of sacubitril/valsartan based on the results of the PARADIGM-HF trial, prescription of sacubitril/valsartan remains rather low.…”
Section: Discussionmentioning
confidence: 99%
“…We found that nearly one in three patients with HFrEF at the VAGLAHS was eligible for treatment with sacubitril/valsartan. It has been estimated that if the criteria from the PARADIGM‐HF trial are strictly followed, then sacubitril/valsartan should be prescribed to < 25% of patients with HFrEF . Researchers found that 12% of patients in a community HF clinic in the United Kingdom were eligible for sacubitril/valsartan treatment using the PARADIGM‐HF trial criteria .…”
Section: Discussionmentioning
confidence: 99%
“…Although patients eligible for treatment at VAGLAHS were more often elderly and had a higher NYHA functional classification compared with patients treated with sacubitril/valsartan in the PARADIGM‐HF trial, the similarities in most other characteristics suggest that this trial can be generalized to our cohort and that treating these eligible patients at VAGLAHS may also significantly reduce morbidity and mortality. A retrospective study that assessed the eligibility for sacubitril/valsartan in the Swedish population also found that their patients were generally older than those in the PARADIGM‐HF trial, which suggests that further studies in the elderly population may be beneficial …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation